THE IMPACT OF PUBLIC ADMINISTRATION REFORMS ON CIVIL AND POLITICAL RIGHTS IN LITHUANIA AT THE TIME OF THE ECONOMIC CRISIS: CASE STUDY OF THE RIGHT TO APPROPRIATE CONDITIONS OF DETENTION - Milašiūtė, Vygantė (Teisė, 2015)
The article addresses the impact of public administration reforms carried out during the economic crisis on human rights in Lithuania, with a special focus on the right to appropriate conditions of detention. The impact, in this field, of the reforms aimed at improving the quality of legislation, attracting private investments, and reducing administrative costs is examined. It is demonstrated that the expected positive impact of these reforms on the conditions of detention has in practice been limited. The question of a possible impact of these reforms on the complaints filed by convicts deprived of their liberty and respective judicial decisions is also addressed paying special attention to the problem of the amount of compensation as well as broader questions on the link between the economic resources of the state and the amount of compensation for inappropriate conditions of detention.